Економічна сутність та види сучасних індустріальних парків - Chekina, Viktoriia D.; Lischuk, Olexander V. (Institute of Industrial Economics of NAS of Ukraine, 2023)
The idea of creation an optimal environment and ecosystem for the business activity, technology and innovation is not new, but over the years it has not lost its relevance, because today there are already more than 700 industrial parks in different countries of the world, which are a strategic tool for the policy of new economic development.The article analyzes the works devoted to the content of the "industrial park" concept, the definition of its functions, industrial parks’ classification, etc. in order to generalize the approaches and results of studies of the economic essence of industrial parks and propose a modern definition of the concept of "industrial park".It has been established that foreign authors usually do not focus on the definition of the concept of "industrial park", using the definition to identify the compliance of the industrial park with the criteria specified by international associations. The interpretation of the term "industrial park" by Ukrainian researchers is almost identical to the definition provided in the Law of Ukraine "On industrial parks" with some differences related to the methodological aspects of the authors' research.It has been recognized that industrial parks are classified according to the presence of ready-made industrial premises for the implementation of economic activities by residents (Greenfield, Brownfield, Greyfield). They also differ in scale and list of services. Industrial parks can also include research parks, innovation centers, science and technology parks.As a result of summarizing definitions and characteristics of industrial parks given by the researchers, authors present a definition of the term "industrial park" as a territory, specially organized and managed by a specialized company for accommodating new industries with distribution according to certain latest industry functions, provided with infrastructure, energy, legal conditions for creating a pool of users (tenants or owners) with a single development concept and management system.The common features of industrial parks are highlighted – support of a local and/or regional economic development; creating an environment conducive to work with the knowledge base, establishing contacts and exchanging ideas; provision of premises and other support services; connection with one or more higher educational institutions, research institutes; promotion customers’ innovation and competitiveness; assistance in investments in knowledge-intensive business and development of start-ups.Further analysis and evaluation of the functioning of industrial parks should be focused on revealing new aspects of their use in the national economic system in the context of aggravated geopolitical confrontation affecting the economy of Ukraine.